Autenticidad de la donación de Fernán González a San Sebastián de Silos (954) / Regarding the Authenticity of Fernán González’s Donation to San Sebastián de Silos in 954. - Vivancos, Miguel C. (Historia. Instituciones. Documentos, 2017)
RESUMEN: Algunos estudiosos consideran falsos muchos de los documentos del conde Fernán González, entre ellos la carta dirigida al monasterio de San Sebastián de Silos, cuyo original no se ha conservado. En este artículo pretendemos demostrar la autenticidad de esta donación, sobre todo comparando sus fórmulas con las Formulae Visigothicae y las de otros documentos de la época que parecen seguir un formulario común, utilizado en los siglos X y XI en todo el reino de León. ABSTRACT: Many documents associated with Count Fernán González are considered to be falsifications by a number of scholars, including the count’s donation to the monastery of San Sebastián de Silos, whose original has not come down to us. The present article sets out the authenticity of the document, above all by comparing its formulas with the Formulae Visigothicae and those of other, contemporary documents which indicate they were composed using the same formulary, adopted during the tenth and eleventh centuries over the whole of the kingdom of León.